Assessment and Optimisation of Lung Cancer Patients for Treatment with Curative Intent. Issue 11 (November 2016) - Harris, C.; Meek, D.; Gilligan, D.; Williams, L.; Solli, P.; Rintoul, R.C.
Abstract: Over the past decade the field of lung cancer management has seen many developments. Coupled with an ageing population and increasing rates of comorbid illness, the work-up for treatments with curative intent has become more complex and detailed. As well as improvements in imaging and staging techniques, developments in both surgery and radiotherapy may now allow patients who would previously have been considered unfit or not appropriate for treatment with curative intent to undergo radical therapies. This overview will highlight published studies relating to investigation and staging techniques, together with assessments of fitness, with the aim of helping clinicians to determine the most appropriate treatments for each patient. We also highlight areas where further research may be required.